Severance pay - a right or a privilege? - Clerke, Francis Ludlow Longueville (Department of Commercial Law, 2023)
It is widely accepted that an employee should be paid severance pay in the event of him losing his job through no fault of his own. In 1963 the International Labour Organisation ("ILO") reflected upon the predicament of such employees and passed a recommendation that "Some form of income protection should be provided for workers whose employment has been terminated; such protection may include unemployment insurance or other forms of social security, or severance allowance or other types of separation benefits paid for by the employer, or a combination of benefits, depending upon national laws or regulations, collective agreements and the personnel policy of employer."